2020
DOI: 10.2147/cmar.s250890
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA AGAP2-AS1/miR-628-5p/PTN Axis Modulates Proliferation, Migration, Invasion, and Apoptosis of Glioma Cells</p>

Abstract: Long non-coding RNAs (lncRNAs) have been reported to be involved in a variety of cancers, including glioma. However, the exact role and underlying mechanism of lncRNA AGAP2 antisense RNA 1 (AGAP2-AS1) in glioma have not yet been fully elucidated. Methods: The expression levels of AGAP2-AS1, microRNA-628-5p (miR-628-5p) and pleiotrophin (PTN) were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Cell proliferation, apoptosis, migration and invasion were detected by Cell Counting Kit-8 (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Yan et al. confirmed that AGAP2-AS1 regulated the migration, invasion, proliferation and apoptosis of glioma cells via the miR-628-5p/PTN axis ( 46 ). We found that AGAP2-AS1 modulated the proliferation, migration and invasion of CCA, and Ji et al.…”
Section: Discussionmentioning
confidence: 98%
“…Yan et al. confirmed that AGAP2-AS1 regulated the migration, invasion, proliferation and apoptosis of glioma cells via the miR-628-5p/PTN axis ( 46 ). We found that AGAP2-AS1 modulated the proliferation, migration and invasion of CCA, and Ji et al.…”
Section: Discussionmentioning
confidence: 98%
“…23 Furthermore, a study showed that glioma cells proliferation, migration and invasion were promoted, and apoptosis was suppressed by the long non-coding RNA AGAP2-AS1 through miR-628-PTN axis regulation. 24 All these studies have indicated that miR-764 and miR-628 are associated with apoptosis and are closely linked to drug resistance. Moreover, our study found that circ-0007312 and miR-764 can be detected in plasma, indicating their potential to be prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%